2018
DOI: 10.1039/c8ra01094c
|View full text |Cite
|
Sign up to set email alerts
|

Deep eutectic solvent-catalyzed arylation of benzoxazoles with aromatic aldehydes

Abstract: A novel and efficient methodology for the arylation of benzoxazoles with aromatic aldehydes catalyzed by deep eutectic solvent has been developed. The reaction smoothly proceeded with a wide range of substrates to give the desired products in high yields within short reaction time. Deep eutectic solvents are easily recovered and reused without significant loss of catalytic activity. Results and discussion Preparation and characterization of [ZnCl 2 ][ethylene glycol] 4DESs were synthesized by mixing zinc chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 61 publications
(59 reference statements)
5
20
0
1
Order By: Relevance
“…3,4 The stable and efficient LADESs can afford the desired products in high yield and selectivity against the conventional metal halide catalysts. [5][6][7][8][9][10][11] However, some drawbacks such as the use of a large amount of LADESs, difficulty in catalyst recovery and product separation, which can cause environmental pollution and a high-cost to the procedure, limit their application in industrial processes. The development of heterogeneous DES catalysts in organic reactions has become a signicant area of research due to the advantages of these materials over traditional homogeneous DESs such as easy product separation, efficient recovery and reusability, and workup simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The stable and efficient LADESs can afford the desired products in high yield and selectivity against the conventional metal halide catalysts. [5][6][7][8][9][10][11] However, some drawbacks such as the use of a large amount of LADESs, difficulty in catalyst recovery and product separation, which can cause environmental pollution and a high-cost to the procedure, limit their application in industrial processes. The development of heterogeneous DES catalysts in organic reactions has become a signicant area of research due to the advantages of these materials over traditional homogeneous DESs such as easy product separation, efficient recovery and reusability, and workup simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, DESs have been applied to many applications such as electrochemistry, gas adsorption, extraction [16], metal processing, catalysis, drug solubilization vehicles [17], fuel [18], and biodiesel [19]. However, a few studies were reported for using DES as a catalyst or solvent in chemical reactions [2, 20, 21, 22, 23, 24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…The IR features shown in Figure 7 a display the vibration bands at 1084 and 1030 cm –1 , related to the C–C–O vibration of surface-adsorbed EG. 49 , 50 The bands at 1650 and 1460 cm –1 are related to the C=O and pyrrolidinyl groups from the PVP chains. 51 A low intensity band can also be observed for all samples at 856 cm –1 .…”
Section: Results and Discussionmentioning
confidence: 99%